(3Sde GdhUhd Edi WHbGJ GdaMhds - (3eUWai Hf YHO Gddg, cGJH LdHj, GdeYQha HGdMGL NdjaI,J (B1067 (3g` s ((3eUWai Hf YHO Gddg GdbSWfWjfi s)
(3ChdgG (B:s
(3HGH GdCda aUd CHGf s
(3BNQgG (B:s
(3GdMeO ddg Ydi GdJeGe s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B262s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B154 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs